THE LEVEL OF ALGEBRAIC REASONING THINKING AMONG MIDDLE SCHOOL LEARNERS AND ITS RELATIONSHIP TO THE PRODUCTIVE DESIRE OF THE LEARNERS - Researcher: Adoan Diab Ghanem; Doctor: Natalie Maamari (Scholars Digest Publishing, 2023)
The study aimed to identify the level of algebraic inference thinking among students in the intermediate stage in Iraq, and to identify the level of desire to see mathematics as a useful and useful science among students in the intermediate stage in Iraq, in addition to studying the relationship between the level of algebraic inference thinking and the desire to see mathematics. As a useful and useful science for students in the intermediate stage in Iraq. It also aimed to identify the differences between the mean scores according to the variables of gender and the level of academic achievement in the level of performance on the algebraic reasoning thinking tests and the desire to see mathematics as a useful and useful science. To achieve these goals, the researcher used the analytical descriptive approach, where the research sample consisted of (60) male and female students in the intermediate stage in Iraq for the academic year (2022-2023). Where the study tools were applied to them, represented by a measure of the level of algebraic inference thinking, and a measure of productive desire. Intermediate stage learners and productive desire, and there is a statistically significant difference between the mean scores of middle stage learners on the algebraic reasoning thinking scale according to the variable (gender) in favor of males, and there is a statistically significant difference between the mean scores of middle stage learners on the scale of the desire to see mathematics as a useful science It is useful according to the variable (sex), in favor of females, and there is a statistically significant difference between the mean scores of middle school learners on the algebraic reasoning thinking scale according to the variable (achievement level in mathematics) in favor of students with a high level of achievement, and there is a statistically significant difference between the mean scores of learners Intermediate stage on the scale of the willingness to see mathematics as a useful and beneficial science according to the variable (achievement level in mathematics) in favor of students with a high level of achievement.
Keywords: algebraic reasoning thinking, productive desire, middle stage.